South Korean Health Diplomacy in Facing COVID-19 - Alwafi Ridho Subarkah; Ahmad Saifuddin Bukhari (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2020)
This study aims to discuss the economic impact caused by the COVID-19 virus outbreak, and look at South Korea's steps in suppressing the spread of the COVID-19 virus and diplomatic steps to help three priority countries namely the United States, United Arab Emirates, and Indonesia. This study uses qualitative research methods that use the concept of health diplomacy, and data collection techniques by conducting library research. The results of this study indicate the global economic and health impacts, collaboration of various parties by conducting health diplomacy is a solution in an effort to improve health and relations with various countries. South Korea conducts health diplomacy in the form of rapid test kits to detect the spread of the COVID-19 virus to America because there is an agreement on currency exchange and new virus cases there, the UAE maintains cooperation in various sectors, and Indonesia as an important partner in ASEAN to realize the new vision of South Korea. So health diplomacy is not just about health in the face of COVID-19, but also to improve relations between countries.